Antifungal Activity of Quaternary Pyridinium Salts Against Fusarium culmorum in Wheat Seedlings - Tamara Siber; Elena Petrović; Jasenka Ćosić; Valentina Bušić; Dajana Gašo-Sokač; Karolina Vrandečić (Applied Sciences)
Wheat (Triticum aestivum L.) is a major cereal crop globally, but its production is increasingly threatened by fungal pathogens, particularly Fusarium culmorum (Wm. G. Sm.) Sacc., which causes seedling blight and root rot, leading to yield losses and mycotoxin contamination. Conventional control strategies, such as crop rotation and the use of fungicides, are often inadequate and contribute to the development of resistance, particularly with the overuse of similar modes of action. This study investigated quaternary pyridinium salts—nicotinamide and isonicotinamide derivatives—as potential sustainable antifungal agents. In vivo tests involved treating sterilized wheat seeds grown in sterile sand that had been inoculated with F. culmorum, using compounds previously confirmed to be active in vitro. Disease index, shoot and root length, and fresh and dry biomass were measured. Among the tested compounds, nicotinamide derivatives (2) and (3) showed the lowest disease index (0.9) at a concentration of 10 µg/mL. Most compounds promoted plant and root growth. Isonicotinamide derivatives (6) and (7) at 100 µg/mL increased root dry weight, while compound (6) at 10 µg/mL resulted in the most significant increase in plant length. These findings highlight the dual antifungal and growth-promoting potential of certain eco-friendly derivatives for managing F. culmorum and supporting wheat seedling development.